MODERN METHODS OF TEACHING ENGLISH - Xudoyqulova Sug‘diyona (Ta'lim innovatsiyasi va integratsiyasi, 2023)
ABSTRACT This article highlights several ways to learn English effectively and some of the modern learning technologies in language learning as well. Modern foreign languages are becoming an important component of professional education in society. Such people acquire knowledge first at school, college, lyceum, and then at institutions the main one that helps to learn a foreign language in courses or independently they learn by familiarizing themselves with data sets.